2018
DOI: 10.1002/cphc.201701354
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, Ion Pairing and Aggregation in 1‐Ethyl‐3‐Methylimidazolium‐Based Ionic Liquids Studied by 1H and 19F PFG NMR: Effect of Temperature, Anion and Glucose Dissolution

Abstract: In this work, using H and F PFG NMR, we probe the effect of temperature, ion size/type and glucose dissolution on the rate of transport in 1-ethyl-3-methylimidazolium ([EMIM] )-based ionic liquids by measuring self-diffusion coefficients. Using such data, we are able to establish the degree of ion pairing and quantify the extent of ionic aggregation during diffusion. For the neat 1-ethyl-3-methylimidazolium acetate ([EMIM][OAc]) a strong degree of ion pairing is observed. The substitution of the [OAc] anion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 36 publications
8
53
0
Order By: Relevance
“…23 Measurements of ion self-diffusion coefficients, D self,+ and D , self,-by pulsed-field gradient NMR (PFG-NMR) have provided valuable insight into the underpinnings of ion transport. [24][25][26][27][28][29][30][31][32] In ideal, dilute electrolytes, wherein the activity coefficients of the ions are unity, the relationships between self-diffusion coefficients and ion transport coefficients are relatively simple. In this limit, ionic conductivity is given by the Nernst-Einstein equation, which is often modified to give Eq.…”
Section: List Of Symbols Amentioning
confidence: 99%
“…23 Measurements of ion self-diffusion coefficients, D self,+ and D , self,-by pulsed-field gradient NMR (PFG-NMR) have provided valuable insight into the underpinnings of ion transport. [24][25][26][27][28][29][30][31][32] In ideal, dilute electrolytes, wherein the activity coefficients of the ions are unity, the relationships between self-diffusion coefficients and ion transport coefficients are relatively simple. In this limit, ionic conductivity is given by the Nernst-Einstein equation, which is often modified to give Eq.…”
Section: List Of Symbols Amentioning
confidence: 99%
“…Pioneering work from Pregosin has shown that through suitable analysis of diffusion data obtained by pulsed‐field‐gradient (PFG) NMR measurements it is possible to understand ion pairing and aggregation in reactions catalysed by transition metal salts. This methodology was recently used to study the effect of temperature, type of anion and presence of additives onto ion pairing and aggregation of imidazolium‐based ionic liquids as well as for studies of deep eutectic solvents . Similar studies on polyaromatic hydrocarbon aggregation, in particular on the effect of attached functional groups on aggregation, have recently been reported .…”
Section: Introductionmentioning
confidence: 98%
“…Previously, the tendency for selfaggregation has been observed also in several ILs. 14,23,24 Analysis of the diffusion data in Figure for phenol show an upper critical solution temperature at 340 K and 33.9 wt% phenol, which is the critical point for the mixture where the two liquids become in one phase and completely miscible. 25 Comparing the diffusivity of Ch + OH and Ch + aliphatic, it can be seen that as fluidity increases the difference between the Ch + OH and Ch + aliphatic diffusion coefficients increases (see ESI).…”
Section: Diffusion Of Species In Ethalinementioning
confidence: 99%
“…Previously, PFG NMR has showed its usefulness in characterizing the mobility of different species, and examining solvent -solvent and solvent -solute interactions in ionic liquids (ILs) and DESs. [11][12][13][14][15] In this study, PFG NMR, 2D nuclear Overhauser effect spectroscopy (NOESY) NMR and dynamic light scattering (DLS) are used to study the solvent -solute interactions and phase behavior of three alcohols, namely glucose, 1-pentanol and phenol, in Ethaline. Previous studies showed that a low surface tension increased extraction efficiency for thiophene and related compounds.…”
mentioning
confidence: 99%